A case-control study and analyze the epidemiological importance risk of family history of psoriasis - Anca Chiriac; Caius Solovan; Anca E Chiriac; Liliana Foia; Piotr Brzezinski (Our Dermatology Online, 2014)
We have conducted a case-control study to analyze the epidemiological importance risk of family history of psoriasis. The retrospective study was done on 1236 patients diagnosed with psoriasis on clinical and histopathological grounds, between 2004-2011, in an Out-patient Clinic in North-Eastern part of Romania.The sex ratio of psoriasis was 1.18:1 (male patients 54.13%, female patients 45.87%), median age at the diagnosis was 29.34±15.24SD; family history of psoriasis (by declaration) was 29.53% (Tabl. I).